Alternative Resolution of Insurance Disputes Through Mediation in Financial Institutions - Muhammad Mukhtar Shidiq; Ro'fah Setyowati (MALIA: Jurnal Ekonomi Islam, 2022)
This study aims to examine the process of resolving insurance disputes through the Alternative Dispute Resolution Institution for the Financial Services Sector (LAPS SJK). The research methodology used in this study is juridical-normative research with a statutory approach. LAPS SJK is an institution that facilitates dispute resolution through non-litigation channels outside of the court system. The findings of the study indicate that insurance disputes can be resolved through mediation or arbitration in LAPS SJK. The mediation process begins with the agreement of the parties to resolve the dispute through mediation at LAPS SJK. After submitting an application through the secretariat office of LAPS SJK, a mediator is appointed to guide the mediation process. This study provides an understanding of the process of resolving insurance disputes through LAPS SJK and provides important information for the parties involved in insurance disputes. _________________________________ Penelitian ini bertujuan untuk mengkaji proses penyelesaian sengketa asuransi melalui Lembaga Alternatif Penyelesaian Sengketa Sektor Jasa Keuangan (LAPS SJK). Metode yang digunakan dalam penelitian ini adalah penelitian yuridis-normatif dengan pendekatan perundang-undangan atau statute approach. LAPS SJK merupakan lembaga yang memfasilitasi penyelesaian sengketa melalui jalur di luar pengadilan (non-litigasi). Hasil penelitian menunjukkan bahwa penyelesaian sengketa asuransi melalui LAPS SJK dapat dilakukan melalui mediasi maupun arbitrase. Prosedur mediasi dimulai dengan kesepakatan para pihak untuk menyelesaikan sengketa melalui mediasi di LAPS SJK. Setelah mengajukan permohonan melalui kantor sekretariat LAPS SJK, mediator akan ditunjuk untuk memandu proses mediasi. Penelitian ini memberikan pemahaman tentang proses penyelesaian sengketa asuransi melalui LAPS SJK dan memberikan informasi penting bagi para pihak yang terlibat dalam sengketa asuransi.